1996
DOI: 10.1182/blood.v88.11.4246.4246
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni excretory circulating cathodic antigen shares Lewis- x epitopes with a human granulocyte surface antigen and evokes host antibodies mediating complement-dependent lysis of granulocytes

Abstract: Parasitic worms of the genus Schistosoma excrete relatively large amounts of immunogenic glycoproteins (circulating cathodic antigen [CCA]) that contain polysaccharide side chains with the trisaccharide Lewis-x (L(ex)) as a repeating unit. These carbohydrates evoke high titers of specific IgM antibodies that cross-react with the repeating L(ex) units on the surface of granulocytes. Consequently this might lead, in the presence of complement, to lysis of the granulocytes. In the present study, this hypothesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Adherent, "angry" PMN may cause local tissue damage and inflammation. It has been reported elsewhere that S. mansoni infection in humans yields anti-Lewis x antibodies that, together with complement, cause lysis of human PMN or HL-60 cell line cells (31,41). Complement might also be involved in gastric damage induced by antibodies to Lewis antigens.…”
Section: Discussionmentioning
confidence: 97%
“…Adherent, "angry" PMN may cause local tissue damage and inflammation. It has been reported elsewhere that S. mansoni infection in humans yields anti-Lewis x antibodies that, together with complement, cause lysis of human PMN or HL-60 cell line cells (31,41). Complement might also be involved in gastric damage induced by antibodies to Lewis antigens.…”
Section: Discussionmentioning
confidence: 97%
“…The present study confirmed the latest explanation when the individuals with CCA-positive and egg-negative, were subjected to follow up for several weeks (up to seven weeks), eventually, all cases were shown to be microscopic positive suggested that the CCA strip method may detect the infection earlier even before the worms start to produce eggs. Another possible explanation of the lower specificity is the general inflammatory biomarkers excreted in the urine, possessing Lewis-X tri-saccharide epitopes, which might cross-react with the CCA strip to illicit a non specific result [23,24]. Indeed Ayele et al [25] reported cross-reactivity in individuals with urinary tract infection (UTI).…”
Section: Discussionmentioning
confidence: 99%
“…Absenting these considerations, several hypotheses have been put forward to explain the false positivity of the CCA-ICT. According to Van Dam et al [ 75 – 76 ], there is the possibility of non-specific cross-reactivity with Lewis-X tri-saccharide epitopes in inflammatory biomarkers present in circulating granulocytes. Lewis-X determinants have also been identified in nematode parasites [ 77 ].…”
Section: Discussionmentioning
confidence: 99%